Liver Stiffness Measurement by Using Transient Elastography in Bangladeshi Patients with Type 2 Diabetes Mellitus and Ultrasonography-Diagnosed Nonalcoholic Fatty Liver Disease - Alam MS (Dove Medical Press, 2021)
Muhammad Shah Alam,1 ABM Kamrul-Hasan,2 Syeda Tanzina Kalam,3 SM Mizanur Rahman,4 Mohammad Izazul Hoque,5 Md Belalul Islam,6 Ajit Kumar Paul7 1Department of Medicine, Army Medical College, Comilla, Bangladesh; 2Department of Endocrinology, Mymensingh Medical College, Mymensingh, Bangladesh; 3Department of Psychiatry, Comilla Medical College Hospital, Comilla, Bangladesh; 4Department of Medicine, CMH and Army Medical College, Comilla, Bangladesh; 5Department of Hepatology, Comilla Medical College, Comilla, Bangladesh; 6Department of Medicine, Comilla Medical College, Comilla, Bangladesh; 7Department of Endocrinology, Maynamati Medical College, Comilla, BangladeshCorrespondence: ABM Kamrul-HasanDepartment of Endocrinology, Mymensingh Medical College, Charpara, Mymensingh, 2207, BangladeshTel +8801711103905Email rangassmc@gmail.comPurpose: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of nonalcoholic fatty liver disease (NAFLD), and the presence of T2DM tremendously drives NAFLD progression. The use of transient elastography (TE) for assessment of NAFLD has been increasing due to its high sensitivity and specificity. This study aimed to measure liver stiffness in patients with T2DM and ultrasonography (USG)-diagnosed NAFLD and assess the correlations between liver stiffness and other clinical and biochemical parameters.Patients and Methods: This cross-sectional study assessed 205 adult patients with T2DM and USG-diagnosed NAFLD who were being treated at a specialized endocrine private practice in Bangladesh. All subjects underwent TE for hepatic fibrosis assessment, which was performed using a FibroScan® 402 device. A fibrosis score ≥ 9.7 kilopascals (kPa) was used to define advanced fibrosis (≥F3).Results: Out of 205 (65.9% female, mean age 45 ± 27 years, 67.3% obese) patients, the frequencies of Grade 1, Grade 2, and Grade 3 fatty liver on USG were 46.3%, 51.2%, and 2.4%, respectively. According to the TE results, 41 (20%) had advanced fibrosis (≥F3). Subjects with advanced fibrosis had a higher body mass index (BMI), higher levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), and higher frequencies of individuals with elevated ALT and AST and advanced fatty liver grades on USG. The fibrosis score (kPa) was strongly and positively correlated with age, BMI, waist circumference, obesity, serum ALT and AST levels, and the fatty liver grade in USG; the AST:ALT ratio did not correlate with kPa.Conclusion: The data showed that 20% of the subjects with T2DM having NAFLD on USG exhibited advanced fibrosis, demonstrating the need for early diagnosis and treatment of NAFLD in T2DM. The use of TE with other serum markers can be helpful for the diagnosis of advanced fibrosis.Keywords: type 2 diabetes, NAFLD, transient elastography, advanced fibrosis, AST:ALT ratio